The Spiny Spinosaurus - OM Books Editorial Team (Uttar Pradesh,India: Om Books International, 2018)
"Taming the Anger Monster" is a heartwarming story about a young boy who learns to manage his anger with the help of his family and a friendly monster. This story helps children understand and cope with their emotions, making it a valuable resource for kids aged 5-8.
"Taming the Anger Monster" is a children's book part of the Life Connect series, focusing on emotional intelligence and anger management. It uses a relatable storyline and lovable characters to teach kids aged 5-8 valuable lessons about understanding and controlling their emotions.
Ages: 5 -8 years
Keywords: OM Books Editorial Team